Songs from the deep - Powell, Kelly, 1991- (Margaret K. McElderry Books, 2019)
Although deadly sirens lurk in the seas around her island town, seventeen-year-old Moira Alexander loves to get close to them and play her violin on the shore. Then the body of twelve-year-old Connor is found on the beach, and the townspeople blame the sirens. Moira and her friend Jude, the lighthouse keeper, are suspicious of these claims and set out to determine the identity of the real killer.